2003
DOI: 10.1007/s00394-003-0426-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the postprandial chylomicron carotenoid responses in young and older subjects

Abstract: The bioavailability of lycopene is apparently impaired in the old,while there is no major difference in the bioavailability of beta-carotene, alpha-carotene and probably lutein. There is also no major effect of age on the cis-trans isomerization of beta-carotene during absorption, and in the intestinal conversion of provitamin A carotenoids into vitamin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…We therefore used an usual number of eight subjects with whom significant differences in carotenoid absorption had been observed previously (Cardinault et al, 2003;Riso et al, 2003;Tesoriere et al, 2004;Blum et al, 2005;Reboul et al, 2005b). Eight non-smoking, healthy male subjects, 20-40 years of age and with a body mass index under 24 kg/m 2 were selected by the Clinical Investigation Center (Sainte Marguerite, Marseille).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore used an usual number of eight subjects with whom significant differences in carotenoid absorption had been observed previously (Cardinault et al, 2003;Riso et al, 2003;Tesoriere et al, 2004;Blum et al, 2005;Reboul et al, 2005b). Eight non-smoking, healthy male subjects, 20-40 years of age and with a body mass index under 24 kg/m 2 were selected by the Clinical Investigation Center (Sainte Marguerite, Marseille).…”
Section: Methodsmentioning
confidence: 99%
“…The major source of provitamin A carotenoids in papaya is b-carotene (15,16). In this study, the highest chylomicron intact appearance of b-carotene was observed in the zinc group, indicating the positive influence of zinc on b-carotene absorption, but not on bioconversion.…”
Section: Influence Of Iron Zinc and Iron1zinc On Chylomicron Intact mentioning
confidence: 57%
“…Chylomicrons were extracted from 1 mL of thawed serum layered under 1 mL NaCl 9 g/L (d51,004 kg/L after ultracentrifugation (150,000 3g for 1 h, at 20˚C)) in the lipid phase. The method had been previously described by Cardinault et al, using plasma (16). The chylomicron supernatant layer was collected, dried under nitrogen and stored at 280˚C until analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first investigation to focus on the effects of vegetable consumption on changes in postprandial PON1 levels. The consumption of vegetables 22,23) or meals supplemented with vitamins 24,25) reportedly increases the amount of lipid soluble antioxidants in postprandial TG-rich lipoproteins. Therefore, colored vegetable consumption is expected to decrease postprandial oxidative stress and increase PON1 activity by protecting PON1 enzymes from oxidative stress-induced inactivation.…”
Section: Discussionmentioning
confidence: 99%